Shaking table tests on seismic response of discontinuous suspended ceilings. (November 2021) - Zhou, Tiegang; Wang, Xin; Liu, Wenhui; Zhang, Zaiyu; Ma, Ben; Tan, Wei
Abstract: In recent earthquakes, we can obtain that the failure of the suspended ceiling systems is part of the most widely reported types of nonstructural damages in building structures. As a nonstructural component, the suspended ceiling systems are not included in the main load-bearing, but the dropping and damage of the suspended ceiling systems resulted in lengthy functional disruptions and extended recovery time. So many researchers studied a large number of ceiling systems in past decades. However, few studies on the application of discontinuous suspended ceiling (DSC) used in some crucial construction with higher rigidity and frequency. Consequently, a full-scale DSC system, including steel runners and metal panels, was designed, fabricated and installed in on a steel frame in this study. Three different ground motions were selected as the vibration input, and the different damages of the ceiling system under different working conditions were found in detail. The results show that the DSC system has good integrity, excellent seismic performance, and four limit states are determined on the basis of this test. Meanwhile, a series of seismic construction measures and suggestions that need to be given attention were proposed in this study, which can be better applied in crucial industrial buildings such as the main control area of nuclear power plants. Highlights: Shaking table test on the overall the DSC system is carried out. The seismic performance of the DSC system is revealed. A series of seismic construction measures and suggestions is proposed.